Methodological standards for qualitative and mixed methods patient centered outcomes research. (23rd December 2020) - Gaglio, Bridget; Henton, Michelle; Barbeau, Amanda; Evans, Emily; Hickam, David; Newhouse, Robin; Zickmund, Susan
Abstract : The Patient-Centered Outcomes Research Institute's (PCORI) methodology standards for qualitative methods and mixed methods research help ensure that research studies are designed and conducted to generate the evidence needed to answer patients' and clinicians' questions about which methods work best, for whom, and under what circumstances. This set of standards focuses on factors pertinent to patient centered outcomes research, but it is also useful for providing guidance for other types of clinical research. The standards can be used to develop and evaluate proposals, conduct the research, and interpret findings. The standards were developed following a systematic process: survey the range of key methodological issues and potential standards, narrow inclusion to standards deemed most important, draft preliminary standards, solicit feedback from a content expert panel and the broader public, and use this feedback to develop final standards for review and adoption by PCORI's board of governors. This article provides an example on how to apply the standards in the preparation of a research proposal.